Laser in the treatment of pressure injury (Research, Society and Development, 2021)
Objective: Describe the use of laser in the treatment of pressure injuries, showing its benefits, its effectiveness and less time for tissue repair Method: This is a literature review of a qualitative nature reviewing articles on the positive effects of laser therapy when using wavelengths, using the following databases for the survey of SCIELO, PubMed works, the inclusion criteria were published between 2013 and 2018 in Portuguese and English, combined using the Boolean AND operator. Results and discussion: Results regarding the effectiveness of the laser action as the main therapy in the re-epithelialization of the injured tissue, the site of laser application and installation by the most prevalent articles in the sacral region. In addition, the use of laser can be recommended in public health and institutions, enabling the reduction of costs and independence for professionals. Conclusion: in this way, laser therapy is an adjunctive treatment with actions capable of contributing to accelerated resolution, resulting from the healing process of tissue injuries, with evidence in the anti-inflammatory, analgesic and healing action, where we form a dynamic role in the biochemical effects. As a result, the use of lasers has had a positive impact, providing well-being and quality of life to customers.